1996
DOI: 10.2134/jeq1996.00472425002500040010x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and Water Present in and Flowing from Root‐Zone Soil

Abstract: From 1990 through 1992, we studied water and nitrate‐nitrogen (NO3‐N) present in the soil and flowing into a subsurface drainage system. Tillages were chisel plow (CP), moldboard plow (MB), no‐till (NT), and ridge‐till (RT). Crops were continuous corn (Zea mays L.) and a corn‐soybean [Glycine max (L.) Merr.] rotation. Tillage and crop only slightly influenced soil NO3‐N and water. Drainage water flows were highest for treatments that minimized soil disturbance and maximized crop residues produced during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 0 publications
5
90
1
Order By: Relevance
“…Figs. 1 and 2 also confirmed previous conclusions that no consistent tillage effects were observed for drain flow and nitrate-N loss in drain flow in the long-term field study (Weed et al, 1995;Weed and Kanwar, 1996). Consistently, the results showed an increase in flow-weighted N concentration with increasing tillage intensity from NT to RT to CP to MP.…”
Section: Simulated and Measured Tillage Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…Figs. 1 and 2 also confirmed previous conclusions that no consistent tillage effects were observed for drain flow and nitrate-N loss in drain flow in the long-term field study (Weed et al, 1995;Weed and Kanwar, 1996). Consistently, the results showed an increase in flow-weighted N concentration with increasing tillage intensity from NT to RT to CP to MP.…”
Section: Simulated and Measured Tillage Effectssupporting
confidence: 88%
“…Tillage had minimum effects on N loss to drain flow under CC as reported by Randall and Iragavarapu (1995), with slightly lower N loss simulated under NT than under MP (5%) and CP (5%) under CS (Table 4). Weed and Kanwar (1996) also reported lower N losses in drain flow under NT from 1990 to 1992 than other tillage (MP, CP, and RT). In contrast, Bakhsh et al (2002) observed the exact opposite tillage effects on N losses in drain flow from 1993 to 1998.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectsmentioning
confidence: 75%
“…Some predictions were inaccurate because tillage effects on infiltration were not simulated. No-till (NT) drained more than moldboard plow (MP) from the Nashua fields possibly because increased plant residue reduced evaporation and rainfall infiltration increased (Weed and Kanwar, 1996). For example, 1990 drainage from plot 2 (MP) was overpredicted while the 1990 drainage from plot 15 (NT) was more accurately predicted (Fig.…”
Section: Drain Flowmentioning
confidence: 99%
“…Dou et al (1995) reported higher fall soil profile NO 3 -for corn combined with a legume green manure cover crop than for soil under corn alone and fertilised at the economic optimum rate. Nevertheless, Weed and Kanwar (1996) and Izaurralde et al (1995) reported lower NO 3 -contents below the root zone and in the drainage water for two types of rotations including both cereals and legumes than for cereal under monoculture. Higher NO 3 -in the soil profile is only indicative of a risk, but does not necessarily translate into significant N losses through denitrification or NO 3 -leaching.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, conflicting evidence exists on the effects of multiple cropping systems including a legume component on N loss reduction (Izaurralde et al 1995;Owens et al 1995;Weed and Kanwar 1996;Høgh-Jensen and Schjoerring 1997;Kuo et al 1997). While legume cover crop can reduce NO 3 -leaching by taking up soil mineral N (Francis et al 1998), the mineralisation of N from legume residues can increase the soluble mineral soil N pool for subsequent transfer if it is released at a time that is not synchronised with plant uptake (Campbell et al 1994).…”
mentioning
confidence: 99%